2017
DOI: 10.3390/ijerph14040375
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor Gene Polymorphism and the Risk of Cardiovascular Disease: A Systemic Review and Meta-Analysis

Abstract: Objective: Few studies have assessed the association between leptin receptor (LEPR) gene polymorphism and the risk of cardiovascular disease (CVD). Of the few epidemiological studies on this topic, the results are still controversial. Methods: PubMed and Embase were screened for studies from their inception to 9 October 2016. The pooled odds ratio (OR) with the corresponding confidence intervals (CI) were used to measure the effect size for studies that reported the association under allelic, homozygous, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Pectin diets can also reduce plasma leptin significantly by more than 60% in an obesity animal model ( 98 ). Leptin receptor (OB-R) can induce cardiac disorders ( 99 ) and also is linked with obesity development, which leads to obesity risk ( 100 102 ). Therefore, POS may affect these molecules by binding OB-R (Figure 5 ).…”
Section: Pos Affect Mitogen-activated Protein Kinases (Mapk) Signalinmentioning
confidence: 99%
“…Pectin diets can also reduce plasma leptin significantly by more than 60% in an obesity animal model ( 98 ). Leptin receptor (OB-R) can induce cardiac disorders ( 99 ) and also is linked with obesity development, which leads to obesity risk ( 100 102 ). Therefore, POS may affect these molecules by binding OB-R (Figure 5 ).…”
Section: Pos Affect Mitogen-activated Protein Kinases (Mapk) Signalinmentioning
confidence: 99%
“…a p<0.05 denoted statistically significant. PPAR-γ: peroxisome proliferator-activated receptorgamma, GG: guanine/guanine, CC: cytosine-cytosine, GC: Guanine/Cytosine analysis showed that Leptin Gln223Arg polymorphism was not significantly associated with cardiovascular disease risk, but have claimed that these findings are still unclear, because the frequency of the 223Arg allele was highly varied in different ethnicities (8).…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, which is one of these genes, is expressed in adipocytes and regulates adiposetissue mass, food intake, energy expenditure, and body weight (7). Many studies have demonstrated that the leptin gene or leptin receptor gene polymorphisms regulate obesity and cardiovascular pathogenesis (8,9). Resistin is a novel hormone that is secreted by adipocytes and its gene is located on chromosome 19p13.2 (10).…”
Section: Introductionmentioning
confidence: 99%
“…CMS, defined as a heterogeneous group of diseases, poses difficult therapeutic management and lacs of accurate molecular predictors [9,10]. Several biomarkers like C-reactive protein (CRP) [11][12][13], adiponectin [14][15][16], leptin [17][18][19][20][21], were studied as predictors for CMS risk, but results proved their failure as promising biomarkers for CMS prevention or disease prognosis prediction.…”
Section: Evidence-based Data On Inflammasome Biomarkers Involvement Imentioning
confidence: 99%